관리 메뉴




수악중독

다항식의 연산 본문

(9차) 수학 I 개념정리

다항식의 연산

수악중독 2016.04.22 10:29

단항식과 다항식





다항식의 덧셈, 뺄셈, 곱셈






곱셈공식


(1) $m(a+b)=ma+mb$,      $m(a-b)=ma-mb$

(2) $(a+b)^2=a^2+2ab+b^2$,      $(a-b)^2=a^2-2ab+b^2$

(3) $(a+b)(a-b)=a^2-b^2$

(4) $(x+a)(x+b)=x^2+(a+b)x+ab$

(5) $(ax+b)(cx+d)=acx^2+(ad+bc)x+db$

(6) $(x+a)(x+b)(x+c)=x^3+(a+b+c)x^2+(ab+bc+ca)x+abc$

(7) $(a+b)^3=a^3+3a^2b+3ab^2+b^3$,          $(a-b)^3=a^3-3a^2b+3ab^2-b^3$

(8) $(a+b)(a^2-ab+b^2)=a^3+b^3$,          $(a-b)(a^2+ab+b^2)=a^3-b^3$

(9) $(a+b+c)^2=a^2+b^2+c^2+2(ab+bc+ca)$

(10) $(a+b+c)(a^2+b^2+c^2-ab-bc-ca)=a^3+b^3+c^3-3abc$

(11) $(a^2+ab+b^2)(a^2-ab+b^2)=a^4+a^2b^2+b^4$





다항식의 나눗셈



저작자 표시 비영리 변경 금지
신고